Relationship Between CEO Power and Firm Value: Evidence from Indonesian Non-Financial Companies - Kharisma Elfianda Hamidlal; Iman Harymawan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This research aims to examine the relationship between the CEO power and firm value of non-financial companies listed on the Indonesia Stock Exchange during the 2014-2018 period. The samples are 322 observations and selected through purposive sampling method. Data was analyzed using multiple linear analysis methods. The results uncovered that ownership power, expert power and prestige power have a positive relationship with firm value. The most probable reasons could be that CEO share ownership encourages better decision-making process that contribute to enhanced corporate value. A longer tenure as a CEO signals high professionalism and expertise of the CEO that led to improved decision quality made by the CEO.